Spinal cord stimulation postconditioning reduces microglial activation through down-regulation of ERK1/2 phosphorylation during spinal cord ischemic reperfusion in rabbits. Issue 14 (26th September 2018) - Dong, Xiuhua; Li, Huixian; Lu, Jiakai; Yang, Yanwei; Jing, He; Cheng, Yi; Jin, Mu; Cheng, Weiping
Abstract : Microglial activation plays a critical role in spinal cord ischemic reperfusion injury. Spinal cord stimulation preconditioning and postconditioning has shown spinal cord protection in ischemic reperfusion injury in animal studies. However, whether spinal cord stimulation could reduce microglial activation is still unclear. In this study, rabbits experienced 28-min infrarenal aorta occlusion and reperfusion for 8 h, 1, 3, and 7 days correspondingly. Immediately after reperfusion, rabbits received spinal cord stimulation of 2 or 50 Hz for 30 min and daily for a week. The results showed that spinal cord stimulation of 2 Hz reduced microglial activation. Microglial activation was accompanied with up-regulated p-ERK1/2, and microglial inhibition by 2 Hz spinal cord stimulation was associated with down-regulated p-ERK1/2. Spinal cord stimulation increased the expression of IL-1β. Our results revealed, for the first time, that spinal cord stimulation postconditioning suppresses microglial activation during spinal cord ischemic reperfusion by down-regulation of p-ERK1/2, which may be the protective mechanism of spinal cord stimulation.